EVALUASI PROGRAM PEMBERDAYAAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Agus Dwi Nugroho; Lestari Rahayu Waluyati; Jamhari Jamhari (Jurnal Kawistara, 2018)
Rural Agribusiness Enterpreneurship Empowerment (RAEE) not only has a beneficial impact for the farmers, but also has many problems. This research was intended 1) to know the performance of RAEE; 2) to know the effectiveness of RAEE on community income and its determining factors; 3) to know the performance and efficiency of Agribusiness Micro Financing Institute (AMFI) and its determining factors. The study was carried out from March until April 2013 in Bantul, Gunungkidul, Kulon Progo, and Sleman Regencies. The respondents were 60 AMFIs and 120 member farmers. RAEE can increase farmer’s income; reduce the number of poor people; increase the number of members, savings, and assets of the combined farmer groups; increase employment, and encourage farmers not to lend to other institutions. But, RAEE also has problems, including deviation of the distribution of RAEE funds, inappropriate use of RAEE funds regard to the planning, problems of bad loans, unofficial legality of most of the AMFIs, and the low capacity of human resources manager. The determinant factors of the RAEE effectiveness are the length of the loan and the type of business. Most of the AMFI in DIY performs poorly. The determinant factors of the AMFI efficiency are the amount of independent capital and the presence of mentoring. The steps to improve RAEE include coaching and supervision of AMFI, control of bad loans, selecting the business types of AMFI, and encouraging AMFI to become an official legal entity.